Outcome of surgery for recurrent anal cancer: results from a tertiary referral centre. (7th September 2018) - Bignell, M.; Chave, H.; Branagan, G.
Abstract: Aim: Chemoradiotherapy remains the first line of treatment for anal cancer with surgery reserved for cancer recurrence or persistence. The low incidence of anal cancer means that the numbers undergoing surgery is small with centralization for excision to regional cancer centres. We present our experience of abdominal perineal excision, with reconstruction of the perineal defect (APERR), within a tertiary centre. Method: Over a 15‐year period, data were collected retrospectively from notes of patients who underwent an APERR. The aim was to look at disease‐free and overall survival and complications associated with flap reconstruction. Results: In the study period, 29 patients [median age = 62 (range: 42–81; interquartile range: 54–68) years] underwent APERR. Median follow‐up was 77 (4–200) months. Thirteen patients died during follow‐up; eight from their disease, with a median survival time of 16 (4–63) months. Five‐year survival was 67%. Nine (31%) patients had recurrence during the follow up period; this was local ( n  = 2), regional ( n  = 4), distant ( n  = 2) or a combination ( n  = 1). Sixteen (55%) patients developed 24 complications, including nine (31%) flap complications and 10 (34%) parastomal hernias. Flap complications were flap failure ( n  = 1) requiring direct closure, flap dehiscence ( n  = 2), necrosis of flap tip ( n  = 1), wound infection ( n  = 4) and a bulky flap ( n  = 1) requiring liposuction. Conclusion: APERR of anal cancer is a feasible technique with excellent oncological treatment and acceptable long‐term complications, although a higher than expected rate of parastomal hernia was noted.